2016
DOI: 10.21608/jssae.2016.39785
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soil Agricultural Productive Capability by Using Remote Sensing and GIS Techniques in Siwa Oasis, Egypt.

Abstract: Siwa Oasis represents one of the most important depressions in the western desert of Egypt. This importance comes from the availability of water resources, which can be used in land reclamation and cultivation projects. Accordingly, the main objective of this work was to evaluate agricultural productivity of soils in Siwa Oasis. For that purpose, 20 geo-referenced soil profiles were dug and sampled based on their development. Forty sixsoil samples were collected from these profiles and analyzed for their physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The practice of intensive agriculture, application of excessive quantity of irrigation water, absence of Nile alluvium and high content of mineral nutrients for vegetation after the construction of high dam and reducing organic matter percentage, specifically in recovered areas (constitute approximately 40 percent of total irrigated farms in Egypt). It was reported that approximately 15% of such agricultural lands are rendered unproductive due to deficiency in nourishing mineral nutrients content as well as entire fertility depletion (El-Ghamry et al, 2009;Elnaggar et al, 2016a;Elnaggar et al, 2016b). There are several reasons for the sharp decline in soil fertility including inadequate fertilization programs, intensive cropping systems, removal of crop residuals, tillage systems, inappropriate cropping systems, inadequate irrigation/drainage systems and soil erosion (Aleminew and Alemayehu, 2020).…”
Section: Soil Fertility Depletionmentioning
confidence: 99%
“…The practice of intensive agriculture, application of excessive quantity of irrigation water, absence of Nile alluvium and high content of mineral nutrients for vegetation after the construction of high dam and reducing organic matter percentage, specifically in recovered areas (constitute approximately 40 percent of total irrigated farms in Egypt). It was reported that approximately 15% of such agricultural lands are rendered unproductive due to deficiency in nourishing mineral nutrients content as well as entire fertility depletion (El-Ghamry et al, 2009;Elnaggar et al, 2016a;Elnaggar et al, 2016b). There are several reasons for the sharp decline in soil fertility including inadequate fertilization programs, intensive cropping systems, removal of crop residuals, tillage systems, inappropriate cropping systems, inadequate irrigation/drainage systems and soil erosion (Aleminew and Alemayehu, 2020).…”
Section: Soil Fertility Depletionmentioning
confidence: 99%
“…Land evaluation is the process used for predicting land use according to its properties (Rossiter, 1996). Extensive information about soil characteristics as well as other vital details for agricultural yield, like water quality, meteorological conditions, and environmental factors are integrated into the land evaluation models (Dengiz and Sağlam, 2012;Elnaggar et al, 2016). The ALES-arid model (Ismail et al, 2005) has been confirmed to be exceedingly effective, user-friendly, and quick.…”
Section: Introductionmentioning
confidence: 99%
“…Land suitability estimation using applications of RS and GIS has been widely applied in Egypt; For example, but not limited to: Agricultural productivity evaluation by using applications of RS and GIS in Siwa Oasis (Elnaggar et al, 2016). Yousif (2018) used RS and GIS for mapping land evaluation in some areas of North-Western Coast.…”
Section: Introductionmentioning
confidence: 99%
“…The Quaternary soils in Siwa Oasis were subjected to a fewpedogenetic,textural and mineralogical studies by earlier workers (e.g. Saleh, 1970;Harga et al, 1975;Aziz and Fanous, 1979;Abdou et al,1980 and1981;El-Khoriby and Issa, 1998;Omran, 2002;Bahanasawy, 2006).The geochemistry of Siwa Oasis soils received attention of recent workers dealing only with soil salinity and degradation (Ismail et al, 2006;Azzam and Salem, 2007;Aly, 2014;Badawy et al, 2015;Elnaggar et al, 2016;Rashed, 2016a and2016b;Rafie, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This activity depends on theavailability of groundwater from about 1199 wells andsprings, which give a total annual discharge of about255 million m3 (Samy, 2010;Elnaggar et al, 2016;El-Saied, 2017).The cultivated lands in Siwa Oasis suffer from salinization problem. The soil salinization is very high in low lands due tohigh salinity in groundwater, quick capillary rise of water in soilsurface, poor workmanship of pumping water, high evaporation andthe high activity of salt weathering (Abdallah, 2007).…”
Section: Introductionmentioning
confidence: 99%